Local Climatic Zoning and Urban Heat Island in Beirut. (2016) - Kaloustian, Noushig; Bechtel, Benjamin
Abstract: Local Climate Zones (LCZ) form a systematic classification scheme that is used nowadays for zoning and categorization of the internal structure of urban areas for various applications including urban climatology. This paper applies local climatic zoning mapping for Beirut, a dense city situated along the Mediterranean Sea, and provides details on the dominating urban form and materials of the city thus contributing to the identification of the main parameters that can promote the formation of an urban heat island (UHI) in the city. The thermal impact of the LCZ is evaluated based on previous Town Energy Balance (TEB) model results.